The dead in dreams : medieval Icelandic conceptions of the unquiet dead - Kanerva, Kirsi (Taylor and Francis Ltd., 2024)
This article examines encounters with the dead in medieval Icelandic contemporary sagas (samtioarsogur) and the changes in cultural conceptions of the power of the dead to return as reflected in these sources. Whereas the better known family sagas (islendingasogur) that were based on centuries-old oral stories portrayed the undead as tangible restless corpses, in contemporary sagas that described more recent historical events the dead appeared in dreams. A short tale called Kumlbua thorn attr provides a case study, to which the examples of the dead appearing in dreams in other sources are contrasted. It is argued that the dead in dreams still acted as moral judges like the tangible restless corpses in the family sagas, but the focus of their attention often shifted from collective to individual responsibility for moral transgressions, thus reflecting the gradual individualisation and interiorisation of medieval Icelandic religious experience. Peer reviewed